PENYELESAIAN PELANGGARAN LALU LINTAS MENGGUNAKAN SANKSI PIDANA DENGAN PENDEKATAN RESTORATIVE JUSTICE - Reza Vahlefi (2022)
Settlement of criminal cases with the concept of restorative justice is a new method in resolving criminal cases in Indonesia. Whereas customary law in Indonesia has used this method since a long time ago, which has become a habit by resolving a problem by way of deliberation to reach consensus. With habits that become values that live in the Indonesian nation, deliberation for consensus is used as a value in the Pancasila State Ideology, the 4th Precept, the value of deliberation for consensus becomes the principle of restorative justice in a justice approach in resolving legal cases. In Purworejo District Court Decision Number 96/Pid.Sus/2018/Pn.Pwr. The Panel of Judges applies the concept of restorative justice in their decisions on traffic cases, this is considered to be able to uphold justice and restore the parties to litigation in traffic criminal cases. The formulation of the problem discussed in this study is about what are the obstacles in the application of restorative justice in the process of resolving traffic cases that cause death and how to apply restorative justice in solving traffic criminal cases that cause death based on (Study Decision Number 96/Pid.Sus /2018/ Pn.Pwr). This research uses normative juridical research methods or legal research libraries, the main data used are primary, secondary, and tertiary data. With a research approach to legislation, cases, and conceptual approaches related to law enforcement and examine the role of law enforcement officers in handling traffic cases with a restorative justice approach. So it is hoped that the settlement of criminal cases with restorative justice can realize justice by paying more attention to the rights of victims, perpetrators and the community.